ANALISIS PERKEMBANGAN DAN PENGGUNAAN ANIMASI SEBAGAI MEDIA IKLAN DI INDONESIA - Paramita Hapsari, S.Ds, M.Ds, Paramita Hapsari, S.Ds, M.Ds (Akademi Komunikasi SAE Indonesia, 2023)
Animated advertising in Indonesia was once considered a significant medium, but its use was still limited, with animation produced exclusively for feature films and television shows at the time. This paper explores the early evolution of Indonesian animation advertising from 1955 to the present. To examine the development and use of animation as an advertising medium in Indonesia, the research method used is descriptive qualitative research method. The findings of this study show how animated advertising has developed into an attractive communication channel in the advertising world from year to year.